Implementation of Creating Shared Value at PT Pegadaian (Persero) Case Study of Alamanda Sejahtera Waste Bank Assistance Program in Bekasi City - Hasan, Andi In’amul; Laksmono, Bambang Shergi (Green Publisher Indonesia, 2023)
This research paper examines the implementation of Creating Shared Value (CSV) at PT Pegadaian (Persero) through its Alamanda Sejahtera Waste Bank Assistance Program in Bekasi City. The study aims to describe the program formulation and implementation of CSV in the waste bank assistance program. CSV, proposed by Michael Porter and Mark Kramer in 2011, emphasizes The importance of creating shared value between companies and society. This concept gives a win-win Solution where companies can achieve their business goals while providing benefits to the community and the environment. The approach and type of research used in this study is a qualitative research with a descriptive approach. The research focuses on PT Pegadaian (Persero), a state-owned financial company that has successfully reduced non-organic waste by 3,600 tons from 2018 to 2022 through its waste bank assistance program. The research contributes to the understanding of CSV implementation in the Indonesian context, focusing on PT Pegadaian (Persero)'s waste bank assistance program. Through this program, the company has not only made a positive impact on the environment by reducing non-organic waste but also created shared value by involving waste bank managers as Pegadaian agents. The findings shed light on the benefits of integrating financial services with waste management initiatives, demonstrating how companies can achieve their business goals while contributing to societal well-being. This research serves as a valuable reference for other financial institutions and organizations interested in implementing CSV and promoting sustainable practices in their operations.